Unraveling the impacts of temperature and vapor pressure deficit on gross primary productivity from current to future scenarios - Chen, Shanshan; Wu, Minchao ; 0000-0003-3557-8462; Zhang, Songlin; Yang, Jie (Journal of Hydrology, 2025)
Elevated air temperature and atmospheric vapor pressure deficit (VPD) are key drivers of plant physiological and ecological processes. However, their relative impacts on vegetation productivity remain difficult to isolate due to the strong coupling between them. This coupling complicates efforts to disentangle independent effects, particularly under compound drought conditions at regional or global scales. We used solar-induced chlorophyll fluorescence and gross primary productivity as proxies for vegetation productivity from 2000 to 2023. Causal relationships among factors and between each factor and SIF were first identified using the convergent cross mapping method. These relationships were then integrated into a partial least squares structural equation model to disentangle the relative effects of air temperature and VPD on SIF. Additionally, we used CMIP6 data under future scenarios to assess their respective future contributions. Our results show that VPD has a dominant negative effect on vegetation productivity. In contrast, air temperature generally exerts a positive influence when the interaction between the two variables is excluded. However, the interaction between VPD and air temperature weakens the positive effect of warming. Furthermore, the adverse impacts of VPD are intensified by other climatic factors. Future projections under SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5 scenarios indicate a continued intensification of VPD’s negative effects and a gradual decline in the positive influence of air temperature by the end of the 21st century. Our study highlights the critical role of VPD in regulating ecosystem functioning. It clarifies the individual contributions of air temperature and VPD to vegetation productivity and underscores the growing threat posed by VPD under global warming, particularly in mid-latitude regions. These findings provide important insights for vegetation management and climate change mitigation strategies.
Publisher Copyright: © 2025 Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: CMIP6; Offset effect; PLS-SEM; Solar-induced chlorophyll fluorescence; Vapor pressure deficit; Warming